The Relationship between Supply Chain Integration, Just-In-Time and Logistics Performance: A Supplier’s Perspective on the Automotive Industry in Malaysia - Akmal Aini Othman; Veera Pandiyan Kaliani Sundram; Nazura Mohamed Sayuti; Atikah Shamsul Bahrin (International Journal of Supply Chain Management, 2016)
This paper examines whether the supply chain integration, just-in-time (JIT) purchasing and JIT manufacturing could impact the logistics performance of suppliers in the automobile industry in Malaysia. An empirical study was conducted in the Malaysia Automobile Industry and the theoretical model was tested using regression analysis. Data were collected using mail questionnaires which were distributed to suppliers of Malaysian automotive manufacturers. The survey was administered to the management level identified from a list of executive personnel and to those who were actually in charge of logistics operations. Among one hundred respondents, 91 were considered as valid from those who practice supply chain integration for their business operations. The findings reveal supply chain integration, JIT purchasing and JIT manufacturing had direct and significant benefits to logistics performance. The scope of this study was by design limited to participant responded within a particular time frame and was only given a single opportunity to respond. The proposed framework provides significant contribution to the performance of logistics operations automotive manufacturing industry and furthermore enables logistics practitioners to gain better understanding of these factors effecting logistics performance. In addition, till to date, no studies has been conducted on the effect of supply chain integration and just-in-time towards logistics performance mainly in the automotive industry particularly in developing county, Malaysia.